2017
DOI: 10.1186/s12864-017-4276-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of endemic clones of toxigenic and non-toxigenic Corynebacterium diphtheriae in Belarus during and after the major epidemic in 1990s

Abstract: BackgroundDiphtheria remains a major public health concern with multiple recent outbreaks around the world. Moreover, invasive non-toxigenic strains have emerged globally causing severe infections. A diphtheria epidemic in the former Soviet Union in the 1990s resulted in ~5000 deaths. In this study, we analysed the genome sequences of a collection of 93 C. diphtheriae strains collected during and after this outbreak (1996 – 2014) in a former Soviet State, Belarus to understand the evolutionary dynamics and vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 54 publications
(68 reference statements)
2
47
0
Order By: Relevance
“…These data do not show any clear variations in the virulence gene repertoire among the strains isolated from patients with disease and asymptomatic carriers. Our previous study showed that the same C. diphtheriae strains can cause diphtheria in some individuals and remain asymptomatic in others [17] .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These data do not show any clear variations in the virulence gene repertoire among the strains isolated from patients with disease and asymptomatic carriers. Our previous study showed that the same C. diphtheriae strains can cause diphtheria in some individuals and remain asymptomatic in others [17] .…”
Section: Resultsmentioning
confidence: 98%
“…Several genes encoding virulence associated proteins such as phospholipase D (Pld), neuraminidase H (NanH), corynebacterial protease (CP40), venom serine protease (Vsp1 and Vsp2), ribosomal-binding protein (Rbp, similar to Shiga-like toxin) and adhesive surface pili are present in different C. ulcerans strains [3] , [9] , [16] . Variations in virulence may depend on the differences in the virulence gene repertoire among individual strains [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively large differences in ANI between groups, 16S rRNA gene conservation between all C. diphtheriae strains was above 99% identity, suggesting that the new clade should be classified as part of the C. diphtheriae species (data not shown). Interestingly, CCUG 5865 was recently used by Grosse-Kock et al ( 2017 ) as an outgroup for their core genome phylogeny because it belonged to lineage-2. The multilocus sequence types of CHUV 2995 and CMCNS703 also cluster with lineage-2 (Figure S1 and Data Sheet 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The MLST genotype of the isolates, ST208, was not reported previously in the C. diphtheriae MLST database and was also never observed previously from another patient in the French national surveillance of C. diphtheriae, suggesting that it is not common. Whole-genome sequencing defines the genetic relatedness among C. diphtheriae isolates with high precision (24)(25)(26). This approach demonstrated that the five isolates belong to the same strain and provided strong support for the hypothesis of cross-transmission among patients and/or contamination from a common source.…”
Section: Discussionmentioning
confidence: 79%